The Role of Forum Kerukunan Umat Beragama (FKUB) of Semarang City Strengthening Pancasila Values among Students through Religious Harmony Socialization - Safina Shazkia Salma; Tutik Wijayanti (Universitas Negeri Semarang, 2026)
Pancasila, as the foundation of the state and the nation's philosophy of life, plays an important role in shaping the younger generation's personalities to be tolerant and civilized. Nevertheless, globalization and the dissemination of digital information can foster intolerance and erode students' national values. This study aims to evaluate how Pancasila values are implemented among students through a socialization program promoting social harmony, organized by the Forum Kerukunan Umat Beragama (FKUB) of Semarang City, and to examine its role in fostering religious moderation and student character. This research uses a qualitative approach, including in-depth interviews with FKUB administrators, school officials, and students involved in outreach activities. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The results show that the FKUB socialization program is able to implement Pancasila values contextually and practically through dialogue, discussion, and interfaith interaction. This program fosters tolerance, mutual respect, and awareness of the importance of harmony in students' social lives. Despite several obstacles, the synergy among FKUB, schools, and local governments was a major factor in the program's sustainability. This study concludes that FKUB's socialization of harmony is an effective strategy for strengthening Pancasila values among students.